1926
DOI: 10.1098/rspb.1926.0032
|View full text |Cite
|
Sign up to set email alerts
|

The fate of the sugar disappearing under the action of insulin

Abstract: The apparent disappearance of sugar injected into normal animals has for a long time puzzled physiological investigators (Bang, Meltzer and Kleiner, Palmer, Woodyatt). When insulin was discovered it was apparent that an agent was available by which the normal processes could be exaggerated, and therefore more easily studied. It was soon shown that the administration of sugar and insulin to the diabetic animal resulted in an increased combustion of carbohydrate and the accumulation of glycogen in the depots. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1926
1926
1989
1989

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The recent experiments by Lesser and his co-workers (36), by Cori and Cori (37), and by Best, Dale, Hoet and Marks (38,39), and also the clinical studies by Lawrence (40), have confirmed the opinion originally expressed by Dale (41) that the ultimate fate of the blood glucose is its con version into glycogen or its complete oxidation to water and carbon dioxide. Nevertheless, an important part of the problem of the effect of insulin on carbohydrate metabolism remains to be elucidated, namely, the discovery of the intermediate stages.…”
Section: Discussionsupporting
confidence: 69%
“…The recent experiments by Lesser and his co-workers (36), by Cori and Cori (37), and by Best, Dale, Hoet and Marks (38,39), and also the clinical studies by Lawrence (40), have confirmed the opinion originally expressed by Dale (41) that the ultimate fate of the blood glucose is its con version into glycogen or its complete oxidation to water and carbon dioxide. Nevertheless, an important part of the problem of the effect of insulin on carbohydrate metabolism remains to be elucidated, namely, the discovery of the intermediate stages.…”
Section: Discussionsupporting
confidence: 69%
“…It seemed logical to suppose that the effects of insulin were exerted at the very beginning of the scheme for the chemical transformation of glucose, if its influence were to be felt in all the branchings of the metabolic road. 4. No unequivocal, consistently reproducible effect had been obtained on an isolated system in vitro.…”
mentioning
confidence: 74%
“…94 The action in adipose tissue fits the unitary concept, that on muscle protein synthesis does not. 4. The presence as well as the nature of the effects of insulin on metabolic parameters of the liver remain curiously contradictory and difficult to resolve.…”
Section: Barrnett-ball Theorymentioning
confidence: 97%
See 1 more Smart Citation
“…The methods used in this investigation were identical with those used by Best, Hoet and Marks (7). For lactic acid Clausen's method was used.…”
Section: Observations On the Onset O F Rigor Mortismentioning
confidence: 99%